Photovoltaic panel self-cleaning coating resistant to fluoride corrosion

Through the coating composed of silicone modified fluorocarbon resin and curing agent, combined with nano nickel oxide and alkyl fluorosilicone materials, the problem of photovoltaic panels on fluoride corrosion and self-cleaning is solved, and the corrosion resistance and self-cleaning effect is achieved, and the effect of long-term corrosion resistance is achieved. The service life of photovoltaic panels is maintained and efficiently generates power.

CN119242123AActive Publication Date: 2025-01-03ZHUHAI IRIDIUM NANOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202411540854.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-03
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The fluoride corrosion problem of photovoltaic panels in contact with industrial waste leads to degradation of performance and shortened service life, and is difficult to self-clean, affecting power generation efficiency.

Method used

The coating consisting of silicone modified fluorocarbon resin and curing agent is used to introduce chemically inert and nano nickel oxide of fluorocarbon materials to form a passivation layer and barrier layer, and combine alkane fluorosilicone materials to improve hydrophobic oleophobic properties and achieve self-cleaning Function.

Benefits of technology

Effectively resist fluoride corrosion, maintain coating performance, excellent hydrophobic and oleophobic properties and self-cleaning properties, extend the service life of photovoltaic panels and maintain efficient power generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242123A_ABST
    Figure CN119242123A_ABST
Patent Text Reader

Abstract

The invention discloses a fluoride corrosion resistant photovoltaic panel self-cleaning coating which is prepared by reaction of the following raw materials: a component A, a component B and 10-20 parts of nano nickel oxide, the component A is organic silicon modified fluorocarbon resin, the component B is an organic silicon modified fluorocarbon resin curing agent, and the nano nickel oxide is an organic silicon modified fluorocarbon resin curing agent. The component B is prepared from the following components in parts by weight: 100 to 120 parts of hexamethylene diisocyanate tripolymer, 35 to 45 parts of monohydroxyl terminated polydimethylsiloxane and 30 to 35 parts of octafluoro-1, 6-hexanediol; all the parts represent parts by weight. The fluoride corrosion-resistant photovoltaic panel self-cleaning coating disclosed by the invention can effectively resist the corrosion effect of fluoride, and also needs to have an excellent self-cleaning function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and in particular relates to a self-cleaning coating for photovoltaic panels which is resistant to fluoride corrosion. Background Art

[0002] Photovoltaic power generation, as a new type of clean energy, has many advantages over traditional power generation, such as environmental protection, pollution-free, and noise-free. It is a sustainable new energy that my country has vigorously developed in recent years. Distributed photovoltaic power generation has received widespread attention and policy-level favor for its flexibility in geographical layout and efficient supplementary function to the power grid system. The government has vigorously promoted the use of space resources such as rooftops of residential buildings and factory buildings, and installed distributed grid-connected photovoltaic power generation systems, which has greatly promoted the popularization and application of photovoltaic power generation technology. However, with the widespread deployment of distributed photovoltaic power generation systems, the problem of direct contact between photovoltaic panels and the three wastes generated by industry and residents has become increasingly prominent. Wastes generated in the aluminum manufacturing industry, copper smelting process, phosphate fertilizer and phosphoric acid production, cement, ceramic and brick manufacturing, glass and enamel manufacturing, and coal combustion, the potential impact of fluorides on photovoltaic panels has gradually emerged. As the core component of the photovoltaic power generation system, the performance and stability of photovoltaic panels are crucial to the power generation efficiency and long-term stable operation of the entire system. Fluorides in these industrial wastes can be deposited on the surface of photovoltaic panels through natural media such as air or rainwater, causing serious corrosion and damage to the material and performance of photovoltaic panels. The deposition of fluorides will not only reduce the photoelectric conversion efficiency of photovoltaic panels and their power generation capacity, but may also accelerate the aging process of the panels and shorten their service life. In addition, these harmful substances may also form a layer of dirt that is difficult to remove, blocking the light-receiving surface of the photovoltaic panels, further reducing their power generation efficiency. Therefore, the research on self-cleaning coatings for photovoltaic panels to resist fluoride corrosion has become particularly important and urgent. The coating material is required to be able to effectively resist the corrosion of fluorides and also have a self-cleaning function that can automatically remove dirt deposited on the surface of the panel to ensure that the photovoltaic panel always maintains an efficient and stable operating state. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a fluoride-resistant photovoltaic panel self-cleaning coating, which can effectively resist the corrosion of fluorides and also needs to have a self-cleaning function.

[0004] The technical solution adopted by the present invention is:

[0005] A fluoride-resistant photovoltaic panel self-cleaning coating comprises component A and component B, wherein component A is an organosilicon-modified fluorocarbon resin, component B is an organosilicon-modified fluorocarbon resin curing agent, and component B comprises 100 to 120 parts of hexamethylene diisocyanate trimer, 35 to 45 parts of monohydroxy-terminated polydimethylsiloxane, and 30 to 35 parts of octafluoro-1,6-hexanediol; the above parts are all parts by weight; component B is polymerized by hexamethylene diisocyanate trimer, monohydroxy-terminated polydimethylsiloxane, and octafluoro-1,6-hexanediol;

[0006] The preparation of component A comprises the following steps:

[0007] (1) dissolving 60 to 80 parts by weight of hydroxybutyl vinyl ether, 80 to 100 parts by weight of monovinyl-terminated polydimethylsiloxane, 240 to 260 parts by weight of vinyl acetate, and 10 to 15 parts by weight of vinyltrimethoxysilane in an appropriate amount of an organic solvent, and stirring the mixture uniformly;

[0008] (2) introducing an inert gas into the reaction system to expel air and moisture from the system, then adding 400 to 480 parts of chlorotrifluoroethylene into the kettle and mixing thoroughly;

[0009] (3) The temperature of the reaction system is controlled at -8 to -10°C, 8 to 10 parts of initiator are slowly added, and the pressure of the reaction system is controlled at 1.8 to 2.0 MPa. After the reaction is complete, the stirring is stopped after the system temperature returns to room temperature;

[0010] (4) Separating the polymerized product from the unpolymerized monomer in the reaction product by filtering, and removing the solvent in the polymerized product by evaporation to obtain an organosilicon-modified fluorocarbon resin, namely, component A.

[0011] Further, the preparation of component B comprises the following steps:

[0012] S1, dissolving 100-120 parts by weight of hexamethylene diisocyanate trimer, 30-35 parts of monohydroxy-terminated polydimethylsiloxane, and 35-45 parts of octafluoro-1,6-hexanediol in an appropriate amount of organic solvent, stirring at a temperature of T1, and reacting completely;

[0013] S2. Evaporating and removing the solvent to obtain an organosilicon-modified fluorocarbon resin curing agent, namely component B.

[0014] Preferably, the organic solvent in step (1) is a mixed solvent of butyl acetate and acetone in a mass ratio of 7:3.

[0015] Preferably, the inert gas in step (2) is nitrogen.

[0016] Preferably, the initiator in step (3) is any one of azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate.

[0017] Preferably, the initiator is added at a rate of 0.5 parts per minute in step (3).

[0018] Preferably, the filtration operation in step (4) is performed by filtering through a plate-and-frame diatomaceous earth filter.

[0019] Preferably, the organic solvent in step S1 is butyl acetate

[0020] Preferably, the temperature T1 in step S1 is 50-100°C.

[0021] Preferably, the evaporation is performed by rotary evaporation under negative pressure.

[0022] The fluoride-resistant photovoltaic panel self-cleaning coating provided by the present invention has the following beneficial effects:

[0023] 1. It has excellent resistance to fluoride corrosion. The introduction of organic silicon materials in the coating, combined with the chemical inertness of the fluorocarbon material itself, can resist the damage of most fluoride ions and acid-base substances to the chemical composition and physical structure of the coating, and can still maintain good performance of the coating in an acid-base environment; the nickel fluoride precipitation generated by fluoride ions and nickel plays the role of passivation layer and barrier layer, delaying the further penetration of corrosive media into the interior of the coating, and enhancing the coating's resistance to fluoride corrosion.

[0024] 2. It has excellent hydrophobic and oleophobic effects. The addition of single-end fixed flexible silicon greatly improves the ultra-slip performance of the liquid on the coating surface. The use of alkyl fluorosilicone materials improves the chemical composition of the surface and reduces the surface free energy, so that it can have excellent hydrophobic and oleophobic properties, repel various liquid pollutants, and prevent them from adhering to the surface of the photovoltaic panel;

[0025] 3. It has excellent self-cleaning performance. When solid pollutants adhere to the surface of the photovoltaic panel, the low polarity composition of the coating surface can reduce the binding force between the solid pollutants and the coating surface, so that they can be removed from the surface under the action of their own gravity, wind or rainfall, thus keeping the surface of the photovoltaic panel clean for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a surface scanning electron microscope (SEM) image of the fluoride corrosion-resistant photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention.

[0027] Figure 2This is a comparison curve of the transmittance in the visible light region of the photovoltaic panel glass coated with the fluoride-resistant photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention and the untreated photovoltaic panel glass.

[0028] Figure 3 This is the hydrofluoric acid corrosion test result of the fluoride-resistant photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention.

[0029] Figure 4 This is a comparison curve of the power generation efficiency of a photovoltaic panel coated with the fluoride-resistant photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention and an untreated photovoltaic panel before and after being placed in an outdoor environment for a long time. DETAILED DESCRIPTION

[0030] The specific implementation of the present invention is described in detail below in conjunction with specific implementation examples, but the present invention is not limited to the given examples.

[0031] Embodiment 1:

[0032] The specific preparation method of the fluoride-resistant photovoltaic panel self-cleaning coating provided by the present invention is as follows:

[0033] (1) 70 g of hydroxybutyl vinyl ether, 90 g of monovinyl-terminated polydimethylsiloxane, 250 g of vinyl acetate, and 12 g of vinyl trimethoxysilane were dissolved in a mixed solvent of butyl acetate and acetone (ratio of 350 g:150 g), and stirred evenly. The above solution was then transferred to a polymerization reactor, which was flushed with nitrogen to expel all air and moisture, and then 460 g of chlorotrifluoroethylene was added to the reactor, and stirred to mix thoroughly;

[0034] (2) Place the polymerization reactor in an ice-salt water bath at -8 to -10°C, then slowly add 9g of azobisisobutyronitrile as a catalyst into the polymerization reactor through a syringe pump at a rate of 0.5g / min. During the process, the system is sealed to prevent air and moisture from entering the reaction system. After the catalyst is added, the entire reaction system is controlled at 1.8 to 2.0MPa by controlling the monomer tank valve. After reacting for 24 hours, remove the polymerization reactor from the ice-salt water bath, and stop stirring after the system temperature returns to room temperature;

[0035] (3) passing the materials in the polymerization reaction kettle through a plate-and-frame diatomaceous earth filter to separate the polymerized product from the unpolymerized monomers, and subjecting the purified polymerized product to rotary evaporation under negative pressure to remove the solvent, thereby obtaining a silicon-modified fluorocarbon resin synthesized by free radical polymerization, i.e., component A;

[0036] (4) dissolving 110 g of hexamethylene diisocyanate trimer, 32 g of monohydroxy-terminated polydimethylsiloxane, and 40 g of octafluoro-1,6-hexanediol in 175 g of butyl acetate solvent, stirring and reacting in a 60° C. water bath for 4 hours, and then subjecting the product to rotary evaporation under negative pressure to remove the solvent, to obtain a curing agent for a silicon-modified fluorocarbon resin, namely, component B;

[0037] (5) Component A and component B were dissolved in 500 g of butyl acetate, 16 g of nano nickel oxide was added, and the mixture was mixed and stirred at room temperature for 1 hour to obtain a fluoride-resistant photovoltaic panel self-cleaning coating.

[0038] Example 2

[0039] The difference between this embodiment and embodiment 1 is that the added amount of each component is 400 g of chlorotrifluoroethylene, 60 g of hydroxybutyl vinyl ether, 80 g of monovinyl-terminated polydimethylsiloxane, and 10 g of vinyltrimethoxysilane, and the temperature in step (4) is 50° C., and the rest is the same as in embodiment 1.

[0040] Example 3

[0041] The difference between this embodiment and embodiment 1 is that the added amount of each component is 480g of chlorotrifluoroethylene, 80g of hydroxybutyl vinyl ether, 100g of monovinyl-terminated polydimethylsiloxane, and 15g of vinyltrimethoxysilane, the temperature in step (4) is 100°C, and the rest is the same as in embodiment 1.

[0042] Example 4

[0043] The difference between this embodiment and embodiment 1 is that 240 g of vinyl acetate, 8 g of azobisisobutyronitrile, 100 g of hexamethylene diisocyanate trimer, and 35 g of octafluoro-1,6-hexanediol are used. The rest is the same as embodiment 1.

[0044] Example 5

[0045] The difference between this embodiment and embodiment 1 is that 250 g of vinyl acetate, 10 g of azobisisobutyronitrile, 120 g of hexamethylene diisocyanate trimer, and 45 g of octafluoro-1,6-hexanediol are used. The rest is the same as in embodiment 1.

[0046] Example 6

[0047] The difference between this embodiment and embodiment 1 is that 10 g of nano nickel oxide and 30 g of monohydroxyl-terminated polydimethylsiloxane are used. The other contents are the same as those in embodiment 1.

[0048] Example 7

[0049] The difference between this embodiment and embodiment 1 is that 20 g of nano nickel oxide and 35 g of monohydroxyl-terminated polydimethylsiloxane are used. The other contents are the same as those in embodiment 1.

[0050] After the glass substrate used for the photovoltaic panel was rinsed alternately with anhydrous ethanol and deionized water for two times, the coating prepared in the above embodiment was sprayed onto the surface of the photovoltaic glass panel, and the glass panel was kept horizontal during the spraying process. After curing at 50°C for 1 hour, a photovoltaic panel self-cleaning coating resistant to fluoride corrosion was prepared on the surface of the photovoltaic glass panel. Then, the transmittance of the coating in the solar radiation spectrum region, the hydrophobic and oleophobic properties, and the hydrofluoric acid corrosion resistance were tested respectively.

[0051] The coating prepared in the embodiment of the present invention was tested for performance as follows:

[0052] Scanning Electron Microscope Characterization: SEM characterization is performed at SUPRA TM The images were obtained using a 55-degree thermal field emission scanning electron microscope (Zeiss, Germany).

[0053] Visible light transmittance measurement: The transmittance of the samples (coated glass and untreated glass) to visible light was tested using an Agilent Cary5000 UV-visible-near infrared spectrophotometer. The size of the test sample was 7.5 cm × 2.5 cm, and a glass slide of the same size was selected as a control sample during the test. The transmittance of air was set as the baseline for the test. The test wavelength range was 400 nm to 800 nm.

[0054] Contact angle measurement: The contact angle of water droplets / oil droplets (if not otherwise specified, the oils used in the test here are all gasoline, i.e., a mixture of aliphatic hydrocarbons and cycloalkanes) on the coating surface was measured using the KRüSSDSA25S optical contact angle analysis system. For the measurement of the contact angle in a non-moving state, a water droplet / oil droplet (about 10 μL) was first added to the sample surface by a motor-controlled syringe. When the droplet is stable, a side image is taken with a camera, and the software is used for fitting calculation to obtain the static contact angle value of the water droplet / oil droplet on the coating surface.

[0055] Sliding angle measurement: The sliding angle of water / oil droplets on the coating surface was measured using the KRüSSDSA25S optical contact angle analysis system. For sliding angle measurement, a motor-controlled rotatable test platform is used to tilt the sample, and the rotation angle of the platform is displayed in real time on a computer connected to the motor. At the beginning of the test, the initial inclination angle of the platform is maintained at 0°. After a water / oil droplet (~10μL) is added to the coating surface via a syringe, the motor is controlled to rotate the platform. The rotation stops at the moment the droplet begins to slide on the surface, and the rotation angle displayed on the computer is recorded as the rolling angle. Each sample is measured at three different positions to reduce data errors.

[0056] Fluoride corrosion resistance test: First, spray the coating on a 1 square centimeter glass substrate as a test sample, configure a specific concentration (1 mol / L) of hydrofluoric acid as a fluoride simulation substance, and immerse the test sample in the configured hydrofluoric acid to simulate the fluoride corrosion environment. After a specific time, the transmittance and anti-wetting performance of the test sample are used to measure the fluoride corrosion resistance of the coating. Here, when the coating transmittance drops below 90% or the water contact angle drops below 90°, stop the simulated corrosion test and record the time.

[0057] Coating adhesion test: The adhesion of the coating is carried out according to the ASTM D3359 standard. All test samples are cross-cut at intervals of 1 mm with a QHF grid cutter, and then 3MTM 600 tape is firmly attached to the grid area, and then a 2kg weight is placed on the tape-attached area and slid and pressed to make the tape fully contact the test area. After standing still for 90 seconds, the tape is quickly pulled apart in the vertical direction (90°), and the same area is tested twice, and then the remaining part of the coating on the substrate is observed to evaluate the adhesion of the coating. According to the standard, when the coating falls off about 0%, its adhesion is 5B grade; when the coating falls off less than 5%, the adhesion is 4B grade; when the coating falls off less than 15%, the adhesion is 3B grade; when the coating falls off less than 35%, the adhesion is 2B grade; when the coating falls off less than 65%, the adhesion is 1B grade; when the coating falls off more than 65%, the adhesion is 0B grade;

[0058] Coating wear resistance test: Taber wear tester was used to test the coating wear resistance according to ASTM standard test (D4060 standard). During the test, a 100g load grinding wheel ( Industries Cs-10) is used as the wear medium. First, the coating is sprayed onto a specific annular glass substrate, and then fixed to the sample stage of the Taber wear tester. A wear wheel is lowered on each side to closely adhere to the surface of the test sample. When the test starts, the sample stage will rotate with the tested sample. Here, one rotation of the sample is defined as a test cycle. After the test, the wear resistance is measured by calculating the weight loss rate of the sample and the changes in transmittance and anti-wetting properties.

[0059] The weight loss rate is calculated by stopping the wear test and weighing when the coating transmittance drops below 90% or the water contact angle drops below 90°. The formula is as follows:

[0060]

[0061] Coating anti-ultraviolet test: The anti-ultraviolet performance of the coating is tested under a UV lamp with a wavelength of 365nm and a power of 300W. After the sample is irradiated for a specified time, the changes in the transmittance and anti-wetting performance of the sample are tested to measure the UV resistance. Here, when the coating transmittance drops below 90% or the water contact angle drops below 90°, the anti-ultraviolet test is stopped and the time is recorded.

[0062] Coating weather resistance test: The weather resistance of the coating is tested in a constant temperature and humidity chamber. The constant temperature and humidity chamber is set at 50°C and 95% humidity to simulate a high temperature and high humidity environment. After the sample is placed for a specified time, the changes in the transmittance and anti-wetting properties of the sample are tested to measure the weather resistance.

[0063] Comparative test of photovoltaic cell power generation efficiency: During the power generation efficiency test, commercial unpackaged photovoltaic silicon wafers were selected as test photovoltaic cells, and the surface was covered with a glass substrate sprayed with a coating and an untreated glass substrate to compare the effect of the test coating on the power generation efficiency of the battery module. The current density-voltage curve was tested by the Taitaishi PROVA200A solar cell analyzer. The solar light source during the test was provided by the Yiguangke SOLARBEAM-06-3A sunlight simulator, simulating AM1.5 sunlight of about 100mW·cm -2 of radiation intensity.

[0064] The above test method was used to test the performance of the coatings formed by coating the photovoltaic glass panels with the coatings prepared in each embodiment. The results are shown in the following table:

[0065] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Transmittance 92.10% 92.11% 91.94% 92.08% 92.13% 92.27% 91.36% Water contact angle 114.88° 110.29° 118.23° 110.57° 116.17° 115.06° 114.71° Water sliding angle 17.36° 18.25° 17.61° 18.90° 18.14° 17.85° 17.49° Oil contact angle 86.41° 80.56° 87.12° 83.15° 86.91° 85.92° 86.17° Oil sliding angle 3.62° 5.17° 3.31° 4.93° 3.95° 3.77° 3.64° Adhesion 5B 5B 4B 5B 4B 5B 5B Wear resistance 1500 cycles 1520 cycles 1450 cycles 1500 cycles 1410 cycles 1500 cycles 1500 cycles Weight loss rate 4.37% 4.16% 5.77% 4.29% 6.11% 4.62% 4.29% UV resistant 3200 hours 2700 hours 3150 hours 2800 hours 3100 hours 3200 hours 3200 hours Weather resistance 910 hours 850 hours 915 hours 900 hours 900 hours 900 hours 910 hours Corrosion resistance 650 hours 600 hours 660 hours 620 hours 650 hours 600 hours 650 hours

[0066] pass Figure 1 It can be seen that the coating formed by the paint of the present invention is a relatively smooth surface on a macro scale, with almost no microstructure, which can greatly reduce the friction coefficient of the coating surface, making the friction of most liquid and solid pollutants on the surface smaller; at the same time, the smooth surface can reduce the energy barrier for the displacement of pollutants on the surface, so that they can be easily removed from the surface with the help of gravity; and compared with the rough surface, the smooth surface can reduce the refraction and diffuse reflection of light at the interface, so that the overall light transmittance of the coating is maintained at a high level, which can maintain a high light energy intake of the photovoltaic panel and maintain a high level of power generation.

[0067] like Figure 2A comparison curve of the transmittance in the visible light region between the photovoltaic panel glass coated with the coating of the present invention and the untreated photovoltaic panel glass shows that, within the wavelength range of 400-800 nanometers, the transmittance of the coated glass and the untreated glass is not much different, both at a level of about 92%±0.1%, indicating that the coating will not have a significant impact on the appearance of the photovoltaic panel, while maintaining a light transmittance almost equivalent to that of the untreated panel. Coating the coating of the present invention will not have an adverse effect on the power generation efficiency.

[0068] The contact angle of water droplets on the coating surface is greater than 110°, indicating that the coating has excellent hydrophobic properties. Water droplets cannot spread on the surface, and the water sliding angle is less than 19°. Water droplets can easily slide off the surface at a lower inclination angle, effectively preventing the formation of water stains on the surface and reducing pollution. Similarly, the contact angle of oil droplets on the coating surface is greater than 80°, and the sliding angle is also less than 5°, indicating that the coating can avoid the adhesion of oil pollutants on the surface to a great extent, keep the surface of the photovoltaic panel clean, and maintain a high level of power generation.

[0069] Figure 3 The hydrofluoric acid corrosion test results of the coating prepared in Example 1 are shown here. The contact angle, sliding angle and transmittance change of water droplets on the surface are mainly selected as indicators to characterize the fluoride corrosion resistance of the coating. It can be seen that after the coating was soaked in 1M hydrofluoric acid, the contact angle, sliding angle and visible light transmittance of water on its surface did not change significantly within 650 hours. This shows that the coating of the present invention is almost not affected by the corrosion of hydrofluoric acid, and the chemical inertness of the organosilicon-modified fluorocarbon material in the coating of the present invention can resist the corrosion of fluorides; on the other hand, the addition of nano-nickel oxide can make the filler form nickel fluoride after contacting fluoride ions, acting as a passivation layer, blocking the further penetration of fluoride ions, and effectively delaying and avoiding the corrosion of fluoride to the material.

[0070] Figure 4 The comparison curve of power generation efficiency of the photovoltaic panel coated with the coating prepared in Example 1 and the untreated photovoltaic panel before and after being placed in an outdoor environment for a long time is shown. It can be seen from the comparison curve that at the beginning of the test, the open circuit voltage and short circuit current of the two are almost equal, which shows that the coating will not have too much impact on the original performance of the photovoltaic panel, and can maintain the original power generation efficiency of the photovoltaic panel. After 45 days of outdoor placement, the power generation efficiency of the untreated photovoltaic panel has dropped significantly. This is mainly because the accumulation of pollutants on the surface of the photovoltaic panel affects the light intake and reduces the power generation level of the photovoltaic panel; while the photovoltaic panel coated with the fluoride corrosion-resistant coating of the present invention has only a slight decrease in power generation efficiency even after 45 days, indicating that the coating of the present invention has excellent self-cleaning performance, can keep the surface of the photovoltaic panel clean in an outdoor environment, and maintain a high power generation level.

[0071] The present invention has been described in detail above in conjunction with specific embodiments. However, the present invention is not limited to the above description. Various changes made within the knowledge of those skilled in the art without departing from the concept of the present invention still fall within the protection scope of the present invention.

Claims

1. A self-cleaning coating for photovoltaic panels resistant to fluoride corrosion, characterized in that: The invention is prepared by reacting raw materials including the following components: component A, component B and 10-20 parts of nano nickel oxide, wherein component A is an organosilicon-modified fluorocarbon resin, component B is an organosilicon-modified fluorocarbon resin curing agent, and component B includes 100-120 parts of hexamethylene diisocyanate trimer, 35-45 parts of monohydroxy-terminated polydimethylsiloxane and 30-35 parts of octafluoro-1,6-hexanediol; the above parts are all parts by weight; The preparation method of component A comprises the following steps: (1) dissolving 60 to 80 parts by weight of hydroxybutyl vinyl ether, 80 to 100 parts by weight of monovinyl-terminated polydimethylsiloxane, 240 to 260 parts by weight of vinyl acetate, and 10 to 15 parts by weight of vinyltrimethoxysilane in an appropriate amount of an organic solvent, and stirring the mixture uniformly; (2) introducing an inert gas into the reaction system to expel air and moisture from the system, then adding 400 to 480 parts of chlorotrifluoroethylene into the kettle and mixing thoroughly; (3) The temperature of the reaction system is controlled at -8 to -10°C, 8 to 10 parts of initiator are slowly added, and the pressure of the reaction system is controlled at 1.8 to 2.0 MPa. After the reaction is complete, the stirring is stopped after the system temperature returns to room temperature; (4) Separating the polymerized product from the unpolymerized monomer in the reaction product by filtering, and removing the solvent in the polymerized product by evaporation to obtain an organosilicon-modified fluorocarbon resin, namely, component A.

2. The fluoride-resistant photovoltaic panel self-cleaning coating according to claim 1, characterized in that: The preparation of component B comprises the following steps: S1, dissolving 100-120 parts by weight of hexamethylene diisocyanate trimer, 30-35 parts of monohydroxy-terminated polydimethylsiloxane, and 35-45 parts of octafluoro-1,6-hexanediol in an appropriate amount of organic solvent, stirring at a temperature of T1, and reacting completely; S2. Evaporating and removing the solvent to obtain an organosilicon-modified fluorocarbon resin curing agent, namely component B.

3. The fluoride-resistant photovoltaic panel self-cleaning coating according to claim 1, characterized in that: The organic solvent in step (1) is a mixed solvent of butyl acetate and acetone in a mass ratio of 7:

3.

4. The fluoride-resistant photovoltaic panel self-cleaning coating according to claim 1, characterized in that: The inert gas in step (2) is nitrogen.

5. The fluoride-resistant photovoltaic panel self-cleaning coating according to claim 1, characterized in that: The initiator in step (3) is any one of azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate.

6. The fluoride-resistant photovoltaic panel self-cleaning coating according to claim 1, characterized in that: The addition rate of the initiator in step (3) is 0.5 parts / minute.

7. The fluoride-resistant photovoltaic panel self-cleaning coating according to claim 1, characterized in that: The filtration operation in step (4) is performed by filtering through a plate-and-frame diatomaceous earth filter.

8. The fluoride-resistant photovoltaic panel self-cleaning coating according to claim 2, characterized in that: The organic solvent in step S1 is butyl acetate.

9. The fluoride-resistant photovoltaic panel self-cleaning coating according to claim 2, characterized in that: In step S1, T1 is 50-100°C.

10. The fluoride-resistant photovoltaic panel self-cleaning coating according to claim 2, characterized in that: The evaporation is performed by rotary evaporation under negative pressure.

Citation Information

Patent Citations

  • Self-cleaning acid-resistant nano protective coating for photovoltaic glass and preparation method of self-cleaning acid-resistant nano protective coating

    CN116445043A

  • Self-cleaning anti-reflection nano film and preparation method thereof

    CN117025076A

  • Corrosion inhibitor containing alkoxysilanes, fluoro-carbons, a catalyst, and a solvent

    TW202222994A

Cited By

  • A kind of anti-metal dust corrosion coating and its preparation method and application

    CN120310325B